2019
DOI: 10.3389/fmicb.2019.00612
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Cold and Copper Stresses on the Proliferation and Transcriptional Response of Listeria monocytogenes

Abstract: Listeria monocytogenes is a foodborne pathogen that can cause severe disease in susceptible humans. This microorganism has the ability to adapt to hostile environmental conditions such as the low temperatures used by the food industry for controlling microorganisms. Bacteria are able to adjust their transcriptional response to adapt to stressful conditions in order to maintain cell homeostasis. Understanding the transcriptional response of L. monocytogenes to stressing conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 58 publications
0
10
0
Order By: Relevance
“…The genome sequence analysis of List 2-2 strain allowed us to identify the 22 genes previously described involved in the anaerobic pathway of cobalamin biosynthesis. We have observed that the growth of L. monocytogenes in low temperature and copper activates mechanisms in response to stress that allow the bacterium to tolerate these conditions [ 36 , 37 ]. Recently, Ahn et al .…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The genome sequence analysis of List 2-2 strain allowed us to identify the 22 genes previously described involved in the anaerobic pathway of cobalamin biosynthesis. We have observed that the growth of L. monocytogenes in low temperature and copper activates mechanisms in response to stress that allow the bacterium to tolerate these conditions [ 36 , 37 ]. Recently, Ahn et al .…”
Section: Discussionmentioning
confidence: 99%
“…Previously we had observed that the transcriptional response of L. monocytogenes differed when stress factors were presented separately or together. In particular, exposure of List2-2 to low temperature + copper activated different cellular processes from those regulated by cold or copper [ 36 ]. In this study, we observed an increase in the expression of genes associated with the cobalamin pathway when L. monocytogenes was cultured at different times at low temperatures with copper in aerobic conditions.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations